2012
DOI: 10.1116/1.4758924
|View full text |Cite
|
Sign up to set email alerts
|

Identification of residual-type defect on extreme ultraviolet mask by projection electron microscope using Monte Carlo simulation

Abstract: Thin absorber defects called residual-type defects are etching residues that tend to become more discernible as the pattern size of the extreme ultraviolet (EUV) mask shrinks. Projection electron microscope (PEM) images of the residual-type defects with various thicknesses were investigated using Monte Carlo simulation. In the case of the secondary electron image, the thickness of the defect was identified by the defect's signal intensity. It was found that the material and its relative thickness affected the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…[4][5][6][7] In order to accelerate this development program, the optimal inspection condition was investigated by using a computer simulation. [8][9][10][11] We already reported that 16-nm-sized defect on hp 64-nm mask pattern was detectable with a 10-times higher signal intensity than that of the standard deviation of the background intensity level by using the PEM technique when the Ru capped multilayer (ML) was used in EUV mask, 9 and the simulated detectability was found to be in good agreement with experimental results. 7 It was also found that the sensitivity of defect detection was predictable by measuring the secondary electron yield curves of a Ta-based absorber layer and Ru-capped ML.…”
Section: Introductionsupporting
confidence: 73%
“…[4][5][6][7] In order to accelerate this development program, the optimal inspection condition was investigated by using a computer simulation. [8][9][10][11] We already reported that 16-nm-sized defect on hp 64-nm mask pattern was detectable with a 10-times higher signal intensity than that of the standard deviation of the background intensity level by using the PEM technique when the Ru capped multilayer (ML) was used in EUV mask, 9 and the simulated detectability was found to be in good agreement with experimental results. 7 It was also found that the sensitivity of defect detection was predictable by measuring the secondary electron yield curves of a Ta-based absorber layer and Ru-capped ML.…”
Section: Introductionsupporting
confidence: 73%
“…[4][5][6] To accelerate this development program, a better understanding of image formation in PEM and improved prediction capability have become essential. 7 In recent times, the accuracy of simulations using advanced Monte Carlo methods has improved significantly. These simulations take into account the charging and discharging effects, electromagnetic fields, detector configurations, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed explanation of the phenomena was described earlier. 24 By using a B 4 C conductive layer, a residual-type defect (etching residue) 21,35,36 can also be detected with high sensitivity. However, the sensitivity depends on the surface material of the etching residue as shown in Fig.…”
Section: Investigation Of the Impact Of Aspect Ratio And Conductive Lmentioning
confidence: 99%
“…[21][22][23][24][25] The PEM has the advantage of a much higher throughput than what is achievable in the case of a conventional scanning electron microscope (SEM) type inspection system. 9,[11][12][13][21][22][23][24][25][26] That is because PEM probes a sample target with large field illumination, whereas SEM probes a sample with a spot beam. In this paper, we investigated the defect detectability of etched ML-EUV masks, and we propose a better and more feasible structure, which would improve the processing accuracy in working with EB systems.…”
Section: Introductionmentioning
confidence: 99%